2008
DOI: 10.1111/j.1365-2710.2008.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of potentially inappropriate medication in older patients in Slovakia

Abstract: Polypharmacy, immobilization, heart failure and depression were documented as predictors of use of potentially inappropriate medication. In depressive patients, drugs other than antidepressants contributed to the extensive use of potentially inappropriate medication. The observed prevalence of use of potentially inappropriate medication in older hospitalized Slovak patients was lower than the prevalence previously documented in Poland and the Czech Republic, but higher than in Croatia and Turkey. The identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 32 publications
(63 reference statements)
5
43
2
7
Order By: Relevance
“…Increased PIM was found to be associated with some of the important parameters like older patients, polypharmacy, depression, immobilization and hypertension. 27,28 In our study polypharmacy is the only factor associated with use of PIMs, while disease condition and age did not show any significant association. Pharmacists are involved in delivering drugs those prescribed to the patients by the physicians.…”
Section: Original Research Articlementioning
confidence: 72%
“…Increased PIM was found to be associated with some of the important parameters like older patients, polypharmacy, depression, immobilization and hypertension. 27,28 In our study polypharmacy is the only factor associated with use of PIMs, while disease condition and age did not show any significant association. Pharmacists are involved in delivering drugs those prescribed to the patients by the physicians.…”
Section: Original Research Articlementioning
confidence: 72%
“…Pharmacotherapy is considered potentially inappropriate when the risks of its use outweigh its benefits (18)(19)(20).Exposure of the elderly population to this type of medication has been shown to be associated with increased morbidity and mortality, increased the frequency of health service use and higher occurrence of ADR (12,13,15,16,21,22).Studies have shown that the prescription of PIM to Brazilian elderly is commonplace in some different settings (23)(24)(25). However, the number of pharmacoepidemiological studies focusing on the Brazilian hospitalized elderly population during their hospital stay is small (26).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in geriatric prescribing, combinations of medicines which cause drug interactions, fixed combinations, dual therapy, and drugs with questionable therapeutic value should all be avoided (9)(10)(11).The quality of drugs prescription for the elderly may, therefore, be assessed by different indicators. In pharmacoepidemiological studies targeting hospitalized elderly, evaluation of parameters such as the use of potentially inappropriate medication (PIM) and polypharmacy is common (8,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Quanto aos fatores de risco relacionados ao uso de MPI, verificou-se que a polifarmácia e a depressão apresentaram significância estatística quanto a essa associação, corroborando com vários outros autores 9,19,34,35 . Como afirmam Bao e colaboradores 35 , não é de surpreender que a polifarmácia foi um fator fortemente associado ao uso de MPI, visto que pacientes com múltiplos medicamentos em uso tem mais chances de receber uma prescrição inadequada e estão mais propensos a ter múltiplas comorbidades, hospitalizações e consultas com médicos de várias especialidades.…”
Section: Discussionunclassified
“…A polimorbidade foi identificada quando o paciente apresentava quatro ou mais doenças 19 , sendo categorizada em: sim, apresenta polimorbidade (≥ 4 doenças) e não apresenta polimorbidade (0 a 3 doenças). As doenças verificadas nos prontuários médicos dos idosos foram agrupadas de acordo com a Classificação Internacional de Doenças, 10ª revisão (CID-10) 20 .…”
Section: O Variáveis Independentesunclassified